Specific inhibition of lymphokine biosynthesis and autocrine growth using antisense oligonucleotides in Th1 and Th2 helper T cell clones (The Rockefeller University Press, 1988)
T helper cells have recently been divided into two subsets. The Th1 subset secretes and responds to IL-2 in an autocrine manner. The Th2 subset upon mitogen or antigen stimulation releases IL-4. Here we describe a novel technology that allowed us to confirm this distinction. We have used synthetic oligonucleotides complementary to the 5' end of mouse IL-2 and IL-4 to specifically block the biosynthesis of IL-2 or IL-4 in two murine helper T cell clones from the Th1 or Th2 subset. We show that the antisense IL-2 oligonucleotide inhibited the proliferation of the Th1 clone and had no effect on the Th2 clone. In parallel experiments, the antisense IL-4 oligonucleotide blocked the proliferation of the Th2 clone and not the proliferation of the Th1 clone. The inhibition was significantly reversed in both cases by the addition of the relevant lymphokine (IL-2 in the case of the Th1 clone, IL-4 in the case of the Th2 clone). Northern analysis, using cDNA probes specific for the two lymphokines, showed a decrease in the steady-state level of the relevant lymphokine mRNA, suggesting the specific degradation of the mRNA by an RNase H-like enzymatic activity. This strategy, which allows the specific blockade of the biosynthesis of a lymphokine, could be useful for future studies on the role of each T helper subset in physiological immune responses.